HUBUNGAN DISPOSISI MATEMATIS DAN SELF-EFFICACY MAHASISWA - Wanda Tri Utami; Ali Mustadi; Marsigit Marsigit; Ibrahim Ibrahim (Universitas Muhammadiyah Metro, 2021)
The writing of this article is a survey research with the aim of knowing the relationship between mathematical disposition and self-efficacy of PGSD/ PGMI students in universities throughout Indonesia. This study used a total of 37 public and private universities with 357 students using questionnaire data collection techniques. The data obtained were analyzed using quantitative descriptive. In addition, data analysis used Spearman's Rho. The results explained that the mathematical disposition with self-efficacy of PGSD / PGMI students in Indonesia based on the average questionnaire filling reached a correlation coefficient of 0.612 which was included in the very strong category. Sig. Value (2-tailed) obtained 0,000 which is smaller than 0.01 which means that there is a significant relationship between mathematical disposition variables and self-efficacy. This caused a strong positive relationship between mathematical disposition and student self-efficacy.   Abstrak Penulisan artikel ini merupakan penelitian survei dengan tujuan mengetahui hubungan disposisi matematis dan self-efficacy mahasiswa PGSD/PGMI yang berada di Universitas se-Indonesia. Penelitian ini menggunakan subjek yang berjumlah 37 universitas negeri dan swasta dengan 357 mahasiswa dengan tekhnik pengumpulan data penyebaran angket. Data yang diperoleh dianalisis menggunakan deskriptif kuantitatif. Selain itu, analisis data menggunakan Spearman's Rho. Hasil penelitian menjelaskan bahwa disposisi matematis dengan self-efficacy mahasiswa PGSD/PGMI yang berada di Indonesia berdasarkan rata-rata pengisian angket mencapai koefisien korelasi 0.612 yang termasuk dalam kategori sangat kuat. Nilai Sig. (2-tailed) didapat 0.000 yang lebih kecil dari 0.01 yang memiliki makna bahwa terdapat hubungan signifikan antara variabel disposisi matematis dengan self-efficacy. Hal tersebut menyebabkan hubungan positif yang kuat antara disposisi matematis dengan self-efficacy mahasiswa.